Supply, fabricating and installation of the CNC cutting railing (package - 1) for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Retail Scape Limited to supply, fabricating and installation of the CNC cutting railing (package - 1) for the Brac University new campus project.